Usefulness of post mortem determination of serum tryptase, histamine and diamine oxidase in the diagnosis of fatal anaphylaxis - Mayer, D.E.; Krauskopf, A.; Hemmer, W.; Moritz, K.; Jarisch, R.; Reiter, C. (Forensic science international, 2011)
The diagnosis of fatal anaphylaxis can be difficult for clinical features may not always be evident in necropsy. Therefore post mortem determination of tryptase and other blood parameters can be helpful in verifying the diagnosis. We compared post mortem tryptase, histamine and diamine oxidase (DAO) serum levels of two patients who had died after a Hymenoptera sting and one patient who died of bronchospasm during anaesthesia with data obtained from 55 control subjects who had died from other causes than anaphylaxis. In the three anaphylactic cases, serum tryptase level was 880, 68 and 200 μg/l (normal range in living subjects: <11.4 μg/l), histamine was 37.5, 8.5 and 23.2 ng/ml (normal range: <0.3 ng/ml) and DAO was 1, 30 and 4 U/ml (normal range 10–30 U/ml), respectively. Values in the control group were as follows: tryptase 1–340 μg/l (mean 24.2 ± 58.2), histamine 5.0–22.0 ng/ml (mean 14.7 ± 3.9) and DAO 0–114 U/ml (mean 21.1 ± 27.8). 19/55 (34.5%) of the controls had elevated tryptase levels >11.4 μg/l, with four of them showing values >45 μg/ml. Significantly higher histamine levels were seen in blood samples taken more than 24 h post mortem ( p < 0.05), whereas the timing of blood collection had no effect on tryptase and DAO levels. While moderately elevated tryptase levels are common in post mortem sera, values above 45 μg/l may support the diagnosis of fatal anaphylaxis. Strongly elevated histamine levels might give an additional clue on fatal anaphylaxis, whereas DAO does not seem to be helpful.